Research Trends on Problem-Based Learning for Enhancing Critical Thinking Skills Based on Students' Cognitive Styles - Nisa Hidayatullah (Current Educational Review, 2026)
Learning models based on problems also offer a learning framework in which participants are confronted with authentic problems that require deep analysis, problem solving, and critical thinking to achieve a deeper understanding. This research aims to determine research trends on the problem-based learning model for increasing critical thinking ability reviewed from cognitive styles. This research uses a descriptive-analytical method, which aims to understand and describe research trends using a problem-based learning model for increasing critical thinking ability reviewed from the cognitive styles of participants. The data used in this study were obtained from information sources indexed by Google Scholar using analytical tools such as Publish or Perish and Dimension.ai. The data identified and analyzed were publication types, publication sources, and highly cited research titles. The data analysis method used bibliometric analysis assisted by VOS viewer software. The analysis results show that research trends indexed by Google Scholar from 2016 to 2025 experienced fluctuating growth. However, in 2024, there were many documents in the form of articles, proceedings, chapters, preprints, edited books, and monographs discussing studies on the problem-based learning model for increasing critical thinking ability reviewed from cognitive styles. The keywords frequently used in this study are critical thinking, cognitive load, and others.